Fatwa and Its Shariah Methodology in Islamic Finance - Lahsasna, A. (Universiti Sains Islam Malaysia, 2024)
Fatwa plays a very significant role in Shariah by providing different resolutions and solutions to the Muslim community when it is needed to ensure the compliance with principles of Shariah and commends of God. It should be understood that fatwa is not confined to particular section in Islamic law but it covers the entire sections and subsection of Islamic law including business, finance and trade. Today, fatwa takes a different shape in Islamic finance; it is introduced and presented in the industry in the form of resolutions issued by Shariah board members who represent Shariah corporate governance body in the structure of the Islamic financial institutions. The resolution is further structured in the form of Shariah endorsement which is part and parcel of product approval as required by the regulators. The present paper discusses fatwa and its methodology in Islamic finance to ensure a sound process of issuing an accurate resolutions that comply with the rules and guidelines that have been set in Islamic jurisprudence.